Sensory processing, autonomic nervous function, and social participation in people with mental illnesses - Ritsuko Hattori; Keisuke Irie; Taisuke Mori; Kosuke Tsurumi; Toshiya Murai; Hiroyuki Inadomi (SAGE Publishing, 2023)
Introduction This study investigated the relationship between sensory processing, respiratory sinus arrhythmia, and social participation in people with psychiatric disorders. Method This study recruited 30 participants, primarily women, from a psychiatric university hospital with a mental health diagnosis listed in the Diagnostic and Statistical Manual of Mental Disorders Fifth Edition (mean age: 37.7 ± 16.0 years). Sensory processing, autonomic nervous function, and social participation were measured using the Adolescent/Adult Sensory Profile®, respiratory sinus arrhythmia, and World Health Organization Disability Assessment Schedule, respectively. Through mediation analysis, a model wherein sensory processing mediated the relationship between respiratory sinus arrhythmia and social participation was developed. Results Social participation was moderately to highly correlated with Adolescent/Adult Sensory Profile® quadrants (excluding sensory seeking) and respiratory sinus arrhythmia. Furthermore, the mediation analysis revealed that sensory avoiding mediated the relationship between respiratory sinus arrhythmia and social participation, consequently counteracting the direct relationship. Conclusion A mediation model was constructed, which indicated that individuals with psychiatric disorders and low parasympathetic nervous system activity expressed higher sensory processing quadrant of sensory avoiding. Ultimately, this was associated with reduced social participation.